CW ultraviolet and visible laser action from ionized silver in an electron beam generated plasma - Rocca, Jorge J., author; Wernsman, B., author; Mancini, H. L., author; IEEE, publisher (Colorado State University. Libraries, 1990)
Continuous wave laser oscillation was obtained in the 318.1 nm and the 478.8 nm lines of AgII in a neon-silver vapor mixture excited by glow discharge electron beams. Laser output powers of 14 and 60 mW were obtained in the ultraviolet and blue transitions, respectively, using nonoptimized optical cavities.